EFEKTIVITAS BIMBINGAN KELOMPOK UNTUK MENGURANGI PROKRASTINASI AKADEMIK PESERTA DIDIK KELAS XI SMA NEGERI 2 MANDAU KABUPATEN BENGKALIS - Intan; Kardo , Rici; Wae, Rahmawati (IKIP Siliwangi, 2025)
Academic procrastination is one of the problems for students in schools. Academic procrastination is a behavior of delaying academic tasks. The purpose of this study is to: 1) Describe the academic procrastination of students before the implementation of group guidance. 2) Describe the academic procrastination of students after the implementation of group guidance. 3) The effectiveness of group guidance services to reduce academic procrastination of students. This study was conducted using an experimental method of one group pretest-posttest design. The research population involved 32 students. The research sample was 12 students. The sampling technique used purposive sampling technique, namely the technique of determining samples with certain considerations. The research instrument was a Likert scale questionnaire. The validity test using correlation person product moment on 30 students trial resulted in 41 valid items with r count > r table (0.361). The reliability test showed a Cronbach's Alpha value of 0.934. The data analysis technique used was the t-test. The results of this study indicate: 1) Academic procrastination of students before the implementation of group guidance is in the fairly high category with a percentage of 50%, 2) Academic procrastination of students after the implementation of group guidance is in the low category with a percentage of 75%. 3) There is a difference in academic procrastination of students before (pretest) and after (posttest) being given group guidance treatment. Proven by the results of the t-test obtained a value of 2.299 > 1.795 and a significant value of 0.042.